2015
DOI: 10.1074/mcp.m114.038018
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analyses for the Global Proteins in the Brain Tissues of Different Human Prion Diseases*

Abstract: Proteomics changes of brain tissues have been described in different neurodegenerative diseases including Alzheimer's disease and Parkinson's disease. However, the brain proteomics of human prion disease remains less understood. In the study, the proteomics patterns of cortex and cerebellum of brain tissues of sporadic Creutzfeldt-Jakob disease, fatal familial insomnia, and G114V genetic CJD were analyzed with isobaric tags for relative and absolute quantitation combined with multidimensional liquid chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 27 publications
3
39
0
Order By: Relevance
“…change (the proteins with 1.2-fold changes relative to the normal control were based on the published reference [15,16]) with a Q-value less than 0.05, and 2) the third ratio was more than 1.0-fold change with a Q-value less than 0.05.…”
Section: Proteins Identification and Quantificationmentioning
confidence: 99%
“…change (the proteins with 1.2-fold changes relative to the normal control were based on the published reference [15,16]) with a Q-value less than 0.05, and 2) the third ratio was more than 1.0-fold change with a Q-value less than 0.05.…”
Section: Proteins Identification and Quantificationmentioning
confidence: 99%
“…18 Previous proteomics studies of HD include the analysis of Htt protein interactome in mouse and cell models 1921 and mouse brain proteomics studies. 2224 These analyses identified a number of cellular processes and pathways affected in HD, including energy production and metabolism, gene transcription, protein translation, RNA processing, cytoskeleton dynamic, and protein trafficking.…”
Section: Introductionmentioning
confidence: 99%
“…The approach used was utilization of isobaric peptide tags (iTRAQ) and multidimensional LC-MS/MS to identify and differentiate proteins between prion disease affected and normal brain samples. Some of the upregulated proteins observed in the cortex and cerebellum of the patients, when compared to normal brains, were those involved in the metabolism, protein transport, development of nervous system symptoms such as ataxia, and reorganization of neuronal actin structure (Shi et al, 2015; Table 1). Some of the downregulated proteins include those involved in the actin cytoskeleton assembly and retrograde transport from early and late endosomes to the trans-Golgi network (Shi et al, 2015).…”
Section: Brainmentioning
confidence: 98%
“…Some of the upregulated proteins observed in the cortex and cerebellum of the patients, when compared to normal brains, were those involved in the metabolism, protein transport, development of nervous system symptoms such as ataxia, and reorganization of neuronal actin structure (Shi et al, 2015; Table 1). Some of the downregulated proteins include those involved in the actin cytoskeleton assembly and retrograde transport from early and late endosomes to the trans-Golgi network (Shi et al, 2015). Animal studies have shown that prion disease-regulated genes could be found in gene families associated with lysosome organization/biogenesis, immune cell activation/inflammatory response, lipid metabolism, apoptosis, protein biosynthesis/proteolysis, nervous system function/synaptic transmission, and cytoskeleton organization/biogenesis (Rubenstein, 2012).…”
Section: Brainmentioning
confidence: 98%
See 1 more Smart Citation